URGENSI PENERAPAN MANAJEMEN KONFLIK DALAM ORGANISASI PENDIDIKAN - Anwar, Khoirul (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2018)
Conflict can be experienced by anyone, and it can happen anywhere, including at school. Students, teachers, or a principal might face to conflict in a certain period of time. If conflict happened at school is not managed and become destructive, then it can disturb school organization and educational efficiency and effectiveness. Conflict can be a serious problem within an organisation, without considering any form of organization and it’s complexity. If the conflict continuously happen without solution. Therefore, the skills to manage the conflict through conflict management are needed by every leader, including principal to solve various conflict that happen at school’s environment. The principal is demanded to master conflict management skills, thus the conflict happened can get a positive effect to improve the quality of education.The main goal to apply the conflict management within the school organization is to develope and maintain cooperative colaboration among educational organization members, such as:principal, teachers, employees, students and even with people beyond school’s community.Keyword: Conflict, organization, principal and conflict management.